Methods and temperatures of hydration on physiological quality of corn seeds - Zucareli, Claudemir (2011)
The procedure to standardize and increase the water content of seeds is recommended to achieve consistent results and reliable tests for the physiological quality of seeds, such as accelerated aging and controlled deterioration. The study aimed to evaluate the physiological quality of corn seeds after hydration under different methods and temperatures, in order to increase the water content to 15, 20 and 25%. Randomized design were employed completely in a factorial 4 x 2 with four replications. The treatments consisted of four methods of moisture (substrate damp, humid atmosphere, immersion in water and adding the required quantity of water) at two temperatures (20 and 30 °C). After hydration, the seeds were subjected to the following parameters: water content, electrical conductivity, germination and normal seedlings in the first count of germination test, dry pasta portions of air, root and whole plant collected in the first count. The method provides a reduction of the moist atmosphere of the physiological quality of corn seeds in three levels of 30°C water temperature and the method of immersion in water does not alter the physiological quality of corn seeds, being suitable for hydration in order to high water content for 15; 20 and 25%.